Preparation and characterization of Fe3O4@Au-C225 composite targeted nanoparticles for MRI of human glioma - Ge, Yaoqi; Zhong, Yuejiao; Ji, Guozhong; Lu, Qianling; Dai, Xinyu; Guo, Zhirui; Zhang, Peng; Peng, Gang; Zhang, Kangzhen; Li, Yuntao (PLOS ONE, 2018)
Objective To study the characterization of Fe3O4@Au-C225 composite targeted MNPs. Methods Fe3O4@Au-C225 was prepared by the absorption method. The immunosorbent assay was used to evaluate its absorption efficiency at C225 Fc. ZETA SIZER3000 laser particle size analyzer, ultraviolet photometer and its characteristics were analyzed by VSM. the targeting effect of Fe3O4@Au-C225 composite targeted MNPs on U251 cells in vitro were detected by 7.0 Tesla Micro-MR; and subcutaneous transplanted human glioma in nude mice were performed the targeting effect in vivo after tail vein injection of Fe3O4@Au-C225 composite targeted MNPs by MRI. Results The self-prepared Fe3O4@Au composite MNPs can adsorb C225 with high efficiency of adsorption so that Fe3O4@Au-C225 composite targeted MNPs were prepared successfully. Fe3O4@Au-C225 composite targeted MNPs favorably targeted human glioma cell line U251 in vitro; Fe3O4@Au-C225 composite targeted MNPs have good targeting ability to xenografted glioma on nude mice in vivo, and can be traced by MRI. Conclusion The Fe3O4@Au-C225 composite targeted MNPs have the potential to be used as a tracer for glioma in vivo.